Voice and case in finnish in the light of Zabrocki’s theory of person - Bielecki, Robert (Lingua Posnaniensis, 2012)
This paper attempts to demonstrate the properties of the categories of voice and case in Finnish in the light of Zabrocki’s theory of Person. The presented morphosyntactic, syntactic and semantic properties of words taking part in diathesis lead us to formulate sentences (theorems) belonging to the sphere of the postulated grammar of person of this language. In Finnish, particular personal meanings undergo both lexicalization (in the form of appropriate personal pronouns) and grammaticalization (in the form of personal endings). Moreover the Finnish language seems to operate with a collective personal meaning, where three particular communicative statuses do not undergo differentiation. This kind of personal meaning seems to be only grammaticalized in Finnish; it lacks a pronoun lexifying such a collective personal meaning. Because of the high degree of syncretism of the nominative and (endingless) accusative on the one hand and the passive and impersonal voice on the other, Finnish contains significant overlapping between passive structures - where the three personal meanings undergo specification - and impersonal structures - where the three personal meanings undergo unification. Notwithstanding, only in sentences of the type Kana on tapettu ‘One has killed the hen’, ‘The hen has been killed’ (and with smaller probability Kana tapetaan ‘One kills (will kill) the hen’, (‘The hen is (will be) killed’)) do we encounter total ambiguity in respect of the personal meaning semified by the predicate (the collective person vs. third person).